Down-regulation of pluripotency and expression of SSEA-3 surface marker for mesenchymal Muse cells by in vitro expansion passaging. Issue 1 (2nd January 2019) - Fouad, Ali M.; Gabr, Mahmoud M.; Abdelhady, Elsayed K.; Rashed, Sahar A.; Khater, Sherry M.; Zakaria, Mahmoud M.
ABSTRACT: Multilineage differentiating stress enduring (Muse) cells is an adult rare pluripotent subpopulation within mesenchymal stem cells (MSCs). Therefore, the need for multiple passages without losing cell pluripotency is required to satisfy the demand for translation medicine. Hence, this study aims to determine the efficiency of Muse cells as a pluripotent cells during in vitro passaging. confocal microscope analysis and cell count of the expression of stage-specific embryonic-3 (SSEA-3) surface marker and the expression of pluripotent genes by reverse transcriptase-qPCR (RT-qPCR) were used for cultured Muse cells at passage 3, 5, 7, 9 and 11. The results showed gradual down-regulation of SSEA-3 surface marker and pluripotent genes, while at passage 3, cells showed higher efficiency compared to other passages. Taken together, these findings indicate that passage 3 is the peak of Muse cell pluripotency.